Pengaruh Kinerja Keuangan Terhadap Investasi Aktiva Tetap - Karnawiredja, R. Aditya M.; Hidayat, Lukman; Effendy, Marwan (LPPM Institut Bisnis dan Informatika Kesatuan, 2013)
The purpose of this study was to determine the effect of the company's financial performance empirically, either partially or simultaneously to the fixed asset investment. Ratio used to look at the financial performance is return on investment (ROI) and total assets turnover (TATO). The research method used in this research is descriptive method, the method of research which not only gives an overview of these phenomena, but to explain relationships, test hypotheses, make predictions and find meaning and implications of a problem is solved. The data used are secondary data and processed data the authors. This study analyzes the relationship between ROI, TATO and fixed asset investment. The statistical method used is multiple linear regression and tested significance. These results indicate that the variable ROI and TATO simultaneous significant effect on the investment of fixed assets. Tests showed that the partial and variable ROI TATO significant effect on the investment of fixed assets. Keywords: Return On Investment, Total Asset Turnover, Fixed Asset Investment